33 A qualitative analysis of cardiology practitioner opinion regarding the benefits, adverse effects and challenges associated with the potential introduction of public reporting of physician events and results (PROPER) to ireland. (30th September 2020) - Fitzpatrick, N
Abstract : Introduction: The premise behind the public reporting of physician events and results (PROPER) is at first glance straight forward. By periodically publicly reporting physicians' outcomes and events, patients are empowered to make more informed decisions when choosing their doctor. Such a registry helps to redress the information asymmetry found at the core of the decision-making problem for patients when attempting to choose their doctor. Examples of PROPER registries include the NICOR Adult PCI Registry in the UK which reports Percutaneous Coronary Intervention (PCI) outcomes for all operators in the UK. Another example (since 1991) is the New York State Cardiac Registry which publishes risk adjusted outcome statistics for all cardiothoracic surgeons operating in the State of New York. Currently, there are no PROPER registries in Ireland. There has only been publication of institution level outcomes through the National Healthcare Quality Reporting System (NHQRS). We surveyed practicing cardiologists and trainees in Ireland, the aim was to examine their perception of the benefits and potential harms associated with PROPER registries. The potential impact such registries might have on referral patterns, market share, how patients choose their cardiologist and whether risk adjustment algorithms are sufficient to protect against adverse behaviours. Methods: Data was collected by means of a 20-question survey circulated amongst attendees at the Irish Cardiac Society (ICS) Meeting 2019. An electronic copy of the survey was also distributed to cardiology practitioners and trainees known to the author but not encountered at the ICS conference. The questions (see table 1 ) were framed as statements, respondents were then asked to quantify their agreement or disagreement with the statement based on a 5-point Likert scale. Results: A total of 39 responses to the survey were received (estimate 26% of all possible responses). Irish cardiologists are in general optimistic regarding the potential benefits of PROPER. Most markedly at an institution level, 81% agreeing that it would improve patient care. 87% of respondents felt that referrals would be significantly affected by public reporting. 77% felt PROPER would impact market share of public versus private practice. 60% of responders considered mortality to be an appropriate quality assurance metric for cardiology (in contrast to only 15% found in similar studies). An overwhelming 97% of respondents felt that public reporting would affect doctors' willingness to intervene on high risk patients. 87% of respondents felt that PROPER would lead to other adverse behaviours such as 'upcoding' or 'gaming.' Conclusion: In conclusion we see that Irish cardiologists in general hold an optimistic view regarding the potential benefits of PROPER. However, they are also aware of its potential for adverse unintended consequences. Responses to this survey were broadly in keeping with those founds in other studies performed in jurisdictions with active PROPER registries, though there were some notable differences.